2011
DOI: 10.1063/1.3567888
|View full text |Cite
|
Sign up to set email alerts
|

Extensional flow of blood analog solutions in microfluidic devices

Abstract: In this study, we show the importance of extensional rheology, in addition to the shear rheology, in the choice of blood analog solutions intended to be used in vitro for mimicking the microcirculatory system. For this purpose, we compare the flow of a Newtonian fluid and two well-established viscoelastic blood analog polymer solutions through microfluidic channels containing both hyperbolic and abrupt contractions/expansions. The hyperbolic shape was selected in order to impose a nearly constant strain rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
111
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 42 publications
0
111
0
Order By: Relevance
“…The flow behaviour under extensional flow is known to be different from that under shear flow conditions. Sousa et al (2011) 12 investigated the flow behaviour of two viscoelastic fluids, known as blood analogue fluids, and concluded that despite their similar shear rheology, the behaviour under a strong extensional flow is different due to differences in the elastic components of both solutions. Recently, Brust et al (2013) 15 also found that blood plasma revealed a different rheological behaviour when experiencing a shear or an extensional flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow behaviour under extensional flow is known to be different from that under shear flow conditions. Sousa et al (2011) 12 investigated the flow behaviour of two viscoelastic fluids, known as blood analogue fluids, and concluded that despite their similar shear rheology, the behaviour under a strong extensional flow is different due to differences in the elastic components of both solutions. Recently, Brust et al (2013) 15 also found that blood plasma revealed a different rheological behaviour when experiencing a shear or an extensional flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lee et 12 studied the effect of the extensional flow in a hyperbolic converging microchannel using animal blood, human blood and blood analogue fluids, respectively. The importance to study these types of geometries is mainly due to their ability to impose a constant strain rate along the centreline 13,14 and consequently generate strong extensional flows.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind the use of hyperbolic contractions is their ability to impose a nominally constant strain rate ð_ e ¼ du x =dx ¼ constant 6 ¼ 0Þ along the centerline as discussed by James 23 for an axisymmetric configuration. Relevant works in the context of blood flow are those of Sousa et al 24 and Lee et al 25 who studied the effect of the extensional flow in hyperbolic converging microchannels using artificial polymer-based blood analog fluids and in vitro rabbit blood, respectively. Sousa et al 24 used hyperbolic contractions of different Hencky strains to show that two well-established blood analogue fluids with identical steady-shear viscosity, but different extensional rheology, behave very differently when submitted to conditions equivalent to the microcirculation.…”
mentioning
confidence: 99%
“…Sometimes solutions of polyacrylamide are used [3][4] [5]. For testing the basic functionality of the cell seeding chamber a solution of Water an Xanthan (0,05 ma%) has been chosen [5]. The viscosity of the blood substitute was checked with a rheometer Mars 2 (Haake).…”
Section: Blood Substitutementioning
confidence: 99%
“…Non-newtonian blood substitutes are often based on polymer solutions, for example mixtures of water and glycerin or mixtures of water, glycerin and xathan. Sometimes solutions of polyacrylamide are used [3][4] [5]. For testing the basic functionality of the cell seeding chamber a solution of Water an Xanthan (0,05 ma%) has been chosen [5].…”
Section: Blood Substitutementioning
confidence: 99%